Correlation between endurance of deep cervical flexors and lower scapular stabilisers in computer users with chronic neck pain. (17th December 2010) - Arora, Deepti; Veqar, Zubia
Abstract : Chronic neck pain is becoming increasingly prevalent among computer users. Recent studies have identified impaired activation of the deep cervical flexor muscles, in people with chronic neck pain. According to Janda's hypothesis of muscle imbalance, deep cervical flexors and lower scapular stabilisers become inhibited in a predicted pattern (upper crossed syndrome). But the relationship between these muscle groups has not been investigated by a study so far. The study was aimed at investigating the correlation between endurance of deep cervical flexors and lower scapular stabilisers in computer users with chronic neck pain. Fifty computer users (22 males and 28 females) in the age group of 20–30 years participated in the study. The endurance of deep cervical flexors was measured using cranio cervical flexion test. Endurance of lower scapular stabilisers was measured using modified version of the grade 3 standard lower trapezius clinical muscle test position. The endurance of deep cervical flexor muscles correlated significantly with the endurance of lower scapular stabilisers of both the right (r=0.666, p≤0.001) and the left (r=0.662, p≤0.001) side. Results also showed that endurance of deep cervical flexor muscles correlated significantly with VAS scores (r = −0.444, p≤ 0.001) but it had no correlation with the duration of neck pain. There is a positive correlation between the endurance of deep cervical flexors and right and left lower scapular stabilisers in computer users with chronic neck pain.